PENGARUH MOTIVASI INTRINSIK DAN MOTIVASI EKSTRINSIK TERHADAP KINERJA KARYAWAN PT. DAEKYUNG INDAH HEAVY INDUSTRY - Ika Rahmawati (Operations Excellence: Journal of Applied Industrial Engineering, 2014)
Abstract. The purpose of this study is to identify and explain the relationshipbetween intrinsic and extrinsic motivation influence the performance ofemployees of PT. DIHI. The study population was all employees of PT. DIHInumber 251 with sampling techniques disproportionate stratified randomsampling and based formula samples slovin found 154 respondents in the sample.Primary data was collected through questionnaires. Testing the validity andreliability of the questionnaire using the product moment correlation andCronbach's alpha. Data analysis using descriptive analysis, multiple linearregression analysis, hypothesis testing simultaneously (F test), testing thehypothesis partially (t test), and the coefficient of determination. The resultsshowed that the intrinsic and extrinsic motivation partial and simultaneouspositive and significant effect on employee performance. For intrinsic motivation,the most influential dimension is recognition. For extrinsic motivation,dimensions that influence the relationships with colleagues, working conditionsand salaries. Recognition can be a charter provision and development of theprovision of educational training. For working conditions, comfort in the work isnot only a convenient, adequate facilities, conducive and safe environment, butalso the relationship with your supervisor and partners.Keywords: intrinsic motivation, extrinsic motivation, job performance